Multipurpose habitat networks for short‐range and long‐range connectivity: a new method combining graph and circuit connectivity. Issue 2 (14th October 2015) - Rayfield, Bronwyn; Pelletier, David; Dumitru, Maria; Cardille, Jeffrey A.; Gonzalez, Andrew
Summary: Biodiversity conservation in landscapes undergoing climate and land‐use changes requires designing multipurpose habitat networks that connect the movements of organisms at multiple spatial scales. Short‐range connectivity within habitat networks provides organisms access to spatially distributed resources, reduces local extinctions and increases recolonization of habitat fragments. Long‐range connectivity across habitat networks facilitates annual migrations and climate‐driven range shifts. We present a method for identifying a multipurpose network of forest patches that promotes both short‐ and long‐range connectivity. Our method uses both graph‐theoretic analyses that quantify network connectedness and circuit‐based analyses that quantify network traversability as the basis for identifying spatial conservation priorities on the landscape. We illustrate our approach in the agroecosystem, bordered by the Laurentian and Appalachian mountain ranges, that surrounds the metropolis of Montreal, Canada. We established forest conservation priorities for the ovenbird, a Neotropical migrant, sensitive to habitat fragmentation that breeds in our study area. All connectivity analyses were based on the same empirically informed resistance surface for ovenbird, but habitat pixels that facilitated short‐ and long‐range connectivity requirements had low spatial correlation. The trade‐off between connectivity requirements in the final ranking of conservation priorities showed a pattern of diminishing returns such that beyond a threshold, additional conservation of long‐range connectivity had decreased effectiveness on the conservation of short‐range connectivity. Highest conservation priority was assigned to a series of stepping stone forest patches across the study area that promote traversability between the bordering mountain ranges and to a collection of small forest fragments scattered throughout the study area that provide connectivity within the agroecosystem. Landscape connectivity is important for the ecology and genetics of populations threatened by climate change and habitat fragmentation. Our method has been illustrated as a means to conserve two critical dimensions of connectivity for a single species, but it is designed to incorporate a variety of connectivity requirements for many species. Our approach can be tailored to local, regional and continental conservation initiatives to protect essential species movements that will allow biodiversity to persist in a changing climate.